Um estudo retórico do discurso publicitário: a metáfora e sua funcionalidade persuasiva - Pilatti, Patricia Maria (2011)
The present study aims at analysing, based on the Rhetorical theory, the rhetorical arguments used in printed advertisements, focusing the ones in which metaphorical phrases are used as an argumentative/persuasive strategy. The corpus of this research constitutes of advertisements which deal with the most preferred topics by the young audience, both masculine and feminine, taken from nationwide magazines of 2006. The theoretical framework that supports the corpus analysis consists of the Rhetorical theory proposed by Aristotle and Perelman, the advertising theories by Sant Anna, Gomes, Gade and Carrascoza, the theories of metaphor postulated by Richards, Ricoeur, Lakoff and Johnson, as well as the Semiotic theory by Barthes, Barros and Santaella. This study has the purpose of promoting a reflection on the usefulness of Rhetorics as a device of self-defense and acting, verifying that the argumentativity is found in the discursive activity, as well as the globalizing character of Rhetorics is found in printed advertisements.